Association of perchlorate, nitrate, and thiocyanate with age-related macular degeneration in the United States - Shiyu Jia; Qin Liu; Peng Liu; Wenli Zhao; Shanshan Li (PLoS ONE, 2025)
Perchlorate, nitrate, and thiocyanate are endocrine-disrupting chemicals, but their associations with AMD is unclear. This study aims to investigate this relationship. We included 4727 participants aged 40 years and older from the National Health and Nutrition Examination Survey (NHANES) 2005–2008. Logistic regression analysis, restricted cubic spline (RCS), and weighted quantile sum (WQS) were applied to investigate the single, non-linear, and combined effects on AMD risk. Nitrate exposure was positively associated with any AMD risk (OR Any AMD , 1.19; 95% CI, 1.05–1.35; P = 0.010) and early AMD risk (OR Early AMD , 1.19; 95% CI, 1.05–1.36; P = 0.010); compared to the first quartile, the highest quartile of nitrate (OR, 1.94; 95% CI, 1.18–3.19; P = 0.012) and thiocyanate (OR, 1.70; 95% CI, 1.19–2.42; P = 0.006) levels were positively associated with AMD risk. The results of RCS showed a nonlinear relationship between nitrate exposure (P for nonlinearity = 0.020), thiocyanate (P for nonlinearity = 0.041), and AMD risk. WQS analysis indicated a positive relationship between mixed exposure and AMD risk (OR, 1.24; 95% CI, 1.01 to 1.51; P = 0.037). This study indicated that high urinary nitrate and thiocyanate levels were associated with an increased AMD risk among US adults. However, the cross-sectional design precludes causal inference.